2004
DOI: 10.1088/0022-3727/37/19/016
|View full text |Cite
|
Sign up to set email alerts
|

Interface properties of iron oxide films

Abstract: We have investigated in a systematic way the interface properties of Fe 2 O 3 grown on different buffer layers using an electron beam deposition technique. For films deposited directly onto Si(001) substrate and on Al buffer layer, we observed the presence of metallic Fe at the Si(001) and Al interfaces, respectively. We also detected the presence of SiO 2 and Al 2 O 3 by x-ray photoelectron spectroscopy. For Fe 2 O 3 films deposited on Cu buffer layer, however, no other phases were observed at the interface. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…In the Fe 2 O 3 /Cu film (oxidized in the atmosphere), it is observed that copper oxide segregates on the surface of iron oxide [37]. These surface energies imply lower interfacial tension of the Cu 2 O in comparison to other possible compounds.…”
Section: Resultsmentioning
confidence: 99%
“…In the Fe 2 O 3 /Cu film (oxidized in the atmosphere), it is observed that copper oxide segregates on the surface of iron oxide [37]. These surface energies imply lower interfacial tension of the Cu 2 O in comparison to other possible compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The observed B.E. difference between Fe 2p doublet spectra, i.e., between 2p 3/2 and 2p 1/2 is ∼13.4 corresponding to iron oxide (Fe 2 O 3 ) phase [34,41,42].…”
Section: X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 96%
“…Iron oxides can be produced in several ways, such as electron beam deposition, 3 electrochemically 4 and also thermally. When heated to a temperature of 200-300°C, a duplex film is formed with an underlayer of magnetite (Fe 3 O 4 ) and an overlayer composed of hematite (˛-Fe 2 O 3 ).…”
Section: Introductionmentioning
confidence: 99%